Influence of Motivation to Result of Cognitive Learning in Intergrated Natural Sciences Model Team Games Tournament (TGT) Assistance by Yugioh Card - Reda Harwinanda (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The purpose of this study was to examine the effect of motivation on the result of cognitive learning of the model TGT assisted YuGiOh Card. The population in this study were students of class VII semester 1 with the number of 16 students at MTs Baitul Amin Bali. The type of research design used was a pre-experimental design with a one-shot case study. The study used 2 (two) variables examined in this study, namely motivation and result cognitive learning. The method used in data collection in this research is a questionnaire (questionnaire), documentation and test. The collected data were analyzed using simple linear regression. Based on the motivation data obtained using the model TGT assisted by the YuGiOh card in this study, it shows that students who are in the very good motivation category are 62.5% and good categories are 37.5%. Data on students' results cognitive learning from post-test results can be categorized very well by 6%, both by 31%, enough by 44% and less by 19%. The influence of motivation on result cognitive learning using the model TGT assisted YuGiOh card is 27.2% while the remaining 72.8% is influenced by learning readiness, social support, and learning facilities. The results showed that learning motivation had a positive effect on result cognitive learning in science learning using the model TGT assisted by YuGiOhcard.